En Esur ('ein Asawir) III : Excavations in the Bronze Age Cemetery - Dagan, Yehuda (IAA reports., 2021)
This volume is the third in a series of reports documenting excavations at the large protohistoric site of 'En Esur and its extensive burial grounds, located in the northern Sharon plain along a major ancient trade route. The four relatively intact and undisturbed Early Bronze Age burial caves presented in the current volume, excavated in the framework of the Cross Israel Highway Project, revealed over 2000 complete ceramic vessels representing an uninterrupted sequence over several hundred years. These four burial caves comprise an invaluable contribution to our knowledge of the society, trad.